Back to Course

JSS3: MATHEMATICS - 1ST TERM

0% Complete
0/0 Steps
  1. Binary Number System I | Week 1
    5Topics
    |
    1 Quiz
  2. Binary Number System II | Week 2
    6Topics
    |
    1 Quiz
  3. Word Problems I | Week 3
    4Topics
    |
    1 Quiz
  4. Word Problems with Fractions II | Week 4
    1Topic
    |
    1 Quiz
  5. Factorisation I | Week 5
    4Topics
    |
    1 Quiz
  6. Factorisation II | Week 6
    3Topics
    |
    1 Quiz
  7. Factorisation III | Week 7
    3Topics
    |
    1 Quiz
  8. Substitution & Change of Subject of Formulae | Week 8
    2Topics
    |
    1 Quiz
  9. Simple Equations Involving Fractions | Week 9
    3Topics
    |
    1 Quiz
  10. Word Problems | Week 10
    1Topic
    |
    1 Quiz
Lesson Progress
0% Complete

A perfect square with a + sign between the two numbers:

(x + a)2  =  ( x + a) (x  + a)

 x (x + a) + a (x  + a)

 x2 + ax + ax  + a2

 x2 + 2ax  + a2

We can state the above result as follows

The first term squared + twice their product + the square of the second term.

A perfect square with a negative sign between the two numbers:

(x – a)2  =  (x – a) (x – a)

 x(x – a) – a (x – a)

 x2 – ax  – ax  – a2

 x2 – 2ax  – a2

(x – a)2  =   x2 – 2ax + a2.

We can state the above result as follows, the first term squared, twice their product, + the square of the second term.

Example 1

Write down the expansions of the following

a. (y + 8)2 

= (y + 8) (y + 8)

= y (y + 8) + 8 (y + 8)

= y2 + 8y + 8y + 64

= y2 + 16y + 64

b. (y – 5)2 

= (y – 5) (y – 5)

= y (y – 5) – 5 ( y – 5)

= y2 – 5y – 5y + 25

= y2 – 10y + 25

c. (7a -3)2 

=  (7a  -3)  (7a – 3)

= 7a (7a – 3) – 3 (7a – 3)

= 49a2 – 21a – 21a + 9

= 49a2 – 42a + 9

d. (2y – 6)2 

=  (2y – 6) (2y – 6)

= 2y (2y – 6) – 6 (2y – 6)

= 4y2 – 12y – 12y + 36

= 4y2 – 24y + 36

e. (5x  + 4y)2 

=  (5x  + 4y) (5x  + 4y)

= 5x (5x + 4y)   + 4y (5  + 4y)

= 25x 2 + 20xy + 20xy + 16y2

= 25x2 + 40xy + 16y2

Example 2

Factorise the following expressions

i. x2 + 4x + 4

6x

 x2 + 2x + 2x  + 4

(x2 + 2x) + (2x + 4)

 x (x  + 2) + 2(x  + 2)

(x + 2) (x + 2)
= (x + 2)2

ii. x2 + 8x  + 16

7x e1606303081355

 x2 + 4x  + 4x  + 16

 (x2 + 4x)  + (4x  + 16)

x(x + 4 )  + 4(x  +  4)

(x + 4) (x + 4)
=  ( x2 + 4)

iii.  x2 – 6x  + 9

8x e1606303407432

 x2 – 3x  – 3x  + 9

(x2 – 3x) – (3x  – 9)

x(x  – 3) – 3(x – 3)

= (x  – 3)(x  – 3)
= (x  – 3)2

back-to-top
error: